Teknik Shibori Kanoko pada Hobo Bag Berbahan Denim dengan Proses Bleaching - Sapitri, Lutfia Ayu; Suryawati, Suryawati; Sesnawati, Yeni (Universitas Negeri Surabaya, 2024)
The purpose of this research is to evaluate the assessment of denim hobo bags utilizing the shibori kanoko technique with a bleaching process, based on product quality aspects using indicators of performance, aesthetics, features, and style. The research method employed is experimental, specifically the Pre-Experimental Design in the form of a One Shot Case Study with a quantitative approach. A questionnaire consisting of 23 statements was administered to five panelists. The data analysis technique used is descriptive statistical analysis.The results of the research indicate that the assessment of denim hobo bags using the shibori kanoko technique with a bleaching process, based on product quality aspects, resulted in an overall score of 92,2 in the excellent category. The performance indicator received the highest score of 97,3, in the excellent category. The lowest score was obtained by the style indicator, with a score of 89, which still falls within the excellent category. When considering the design, the highest score was achieved by design 5, with a score of 92,8, in the excellent category. The lowest score was obtained by design 2, with a score of 91,5, in the excellent category. These findings demonstrate that the evaluation based on product quality aspects of denim hobo bags using the shibori kanoko technique with a bleaching process is already very good.